Ursodeoxycholyl lysophosphatidylethanolamide inhibits cholestasis- and hypoxia-induced apoptosis by upregulating antiapoptosis proteins - Sellinger, Myra Johanna; Xu, Weihong; Pathil-Warth, Anita; Stremmel, Wolfgang; Chamulitrat, Walee (Experimental biology and medicine, 2015)
An increase of toxic bile acids such as glycochenodeoxycholic acid occurs during warm ischemia reperfusion causing cholestasis and damage in hepatocytes and intrahepatic biliary epithelial cells. We aim to test antiapoptosis effects of ursodeoxycholyl lysophosphatidylethanolamide under cholestatic induction by glycochenodeoxycholic acid treatment of mouse hepatocytes and hypoxia induction by cobalt chloride treatment of intrahepatic biliary epithelial cancer Mz-ChA-1cell line. Such treatments caused marked increases in apoptosis as evidenced by activation of caspase 3, caspase 8 and poly (ADP-ribose) polymerase-1. Co-treatment with ursodeoxycholyl lysophosphatidylethanolamide significantly inhibited these increases. Interestingly, ursodeoxycholyl lysophosphatidylethanolamide was able to increase expression of antiapoptotic cellular FLICE-inhibitory protein in both cell types. Ursodeoxycholyl lysophosphatidylethanolamide also prevented the decreases of myeloid cell leukemia sequence-1 protein in both experimental systems, and this protection was due to ursodeoxycholyl lysophosphatidylethanolamide’s ability to inhibit ubiquitination-mediated degradation of myeloid cell leukemia sequence-1, and to increase the phosphorylation of GSK-3β. In addition, ursodeoxycholyl lysophosphatidylethanolamide was able to prevent the decreased expression of another antiapoptotic cellular inhibitor of apoptosis 2 in cobalt chloride-treated Mz-ChA-1 cells. Hence, ursodeoxycholyl lysophosphatidylethanolamide mediated cytoprotection against apoptosis during toxic bile-acid and ischemic stresses by a mechanism involving accumulation of cellular FLICE-inhibitory protein, myeloid cell leukemia sequence-1 and cellular inhibitor of apoptosis 2 proteins. Ursodeoxycholyl lysophosphatidylethanolamide may thus be used as an agent to prevent hepatic ischemia reperfusion.